Effect of time interval from completion of neoadjuvant chemotherapy to starting of adjuvant chemotherapy after interval debulking surgery on survival of patients with advanced ovarian cancer - Kumari, Asha; Parekh, Chetana; Patel, Shilpa M.; Arora, Ruchi; Tyagi, Vishakha; Padival, Ashika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: To find the effect of time interval between completion of neo adjuvant chemotherapy to the starting of adjuvant chemotherapy on the RFS and OS of patients with advanced ovarian cancers. Methods: It is a retrospective study of 170 patients with histopathological proven epithelial ovarian cancers who received full treatment (NACT+IDS+POAC) at Gujarat cancer Research Institute, Ahmedabad between 2010- 2016. They were assessed and followed up for maximum 5 year. The time interval was defined as period from the completion of NACT including Interval de-bulking surgery to initiation of chemotherapy. Results: Out of 170 patients, 86 patients (50.5%) received adjuvant chemotherapy within 44 days after neoadjuvant chemotherapy while 84 patients (49.4%) received it after 44 days. There was no significant difference in patient characteristics between these two groups. The shorter and longer TI was having recurrence in 40 (53.48%) and47 (55.55%) patients respectively. Whereas overall survival was 67.44% and 47.61% respectively. Conclusions: Our analysis showed that patients with longer time interval >44 days had poorer recurrence free survival and overall survival in comparison to lesser TI group.